Diseño de herramienta para empalme de conductor unipolar aislado dirigido al área eléctrica de Tecnioriente s.a.s - Romero Henao, Yolmar Alexis (Universidad Antonio Nariño, 2021)
The present work was based on the investigation of a tool that performs the splicing process of electric cables, aware that generally in the work of electrical installations, there is a need to perform splicing of insulated wire conductors and that in a high percentage This practice creates inconveniences if it is not executed properly, leading to different failures in electrical installations, such as overloading of the circuits, overheating of conductors, sparks, short circuits and fires, among others, also the use of an inappropriate technique when carrying out the procedure to Joining two or more conductors can present incidents or electrical accidents that put the physical integrity of the technician or professional electrician who manipulates and does this activity at risk. The work is directed to the design of the tool that performs a joint of insulated wire conductors; it does it by means of 7 direct current motors that act from the opposite ends to the tips of the conductor. a pinion mechanism and mechanical parts which perform the work in an encapsulated cabin avoiding direct manual contact of the operator, guaranteeing the quality of the joint and the safety of the electrician. The structural design was carried out from various tests seeking to find the best option to satisfy the need and finally the simulation was carried out with electronic simulation software demonstrating the viability of the project.